Noncontact high sensitivity chipless tag microwave resonator for bitumen concentration measurement at high temperatures. (1st April 2020) - Baghelani, Masoud; Abbasi, Zahra; Daneshmand, Mojgan
Graphical abstract: Highlights: High temperature real-time sensor for bitumen concentration based on microwave resonators. The sensor is a chipless tag especially designed for harsh environmental conditions. Extremely high sensitivity of 500 kHz is achieved due to removing of the substrate of the tag. The chipless sensor is able to measure bitumen concentration at 60 mm distance from the reader. The sensing part consumes zero power so is an ideal option for "mount and leave" applications. Abstract: Real-time water concentration measurement in bitumen is critically important during all operating processes from extraction to refining. Having a low-cost, noncontact sensor that can operate in high temperatures is vital in terms of energy conservation, process optimization and elapsed time. This paper presents a specific design of a microwave coupled split ring resonator-based sensor, with a ground-gap-coupled transmission line as the reader. The tag is a metallic trace with the theoretical capability to sense in ultra-high temperatures far beyond the maximum temperature used in bitumen refineries and is electromagnetically coupled the reader, enhancing the coupling distance up to 60 mm. Therefore, the proposed sensor is well adapted to measure in harsh environmental conditions. Various simulations are conducted and compared against experimental results, verifying the features for the introduced sensor such as the capability to measure at temperatures higher than 200 °C, extremely high sensitivity of 500 kHz (1% of water concentration variation) and measurement in both steady-state and turbulent conditions.